Pengaruh Penggunaan Media Permainan Ludo Terhadap Hasil Belajar Peserta Didik Materi Animalia Kelas X SMAN 8 Luwu Timur - Arvia Larasati; Muh. Rapi; Dahlia Patiung (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2022)
The use of media in learning is very important to improve student learning outcomes. One of the widely used media is game media. This research is a quasi experiment with a non-equivalent control group design. The research objective was to determine the effect of ludo game media on the learning outcomes of class X students of SMAN 8 Luwu Timur. The research was conducted in two classes, X IPA 3 as the experimental class and X IPA 2 as the control class with 18 students each. The research sample was selected by purposive sampling technique. Data was collected through a multiple-choice test with 25 multiple-choice questions. The results of the study were analyzed descriptively and inferentially using the t test. The results showed that the average learning result of the experimental class was 83.11, much higher than that of the control class, which was 60.00. The significance value of the t test shows a value of 0.000 <0.05 (sig @). So it can be concluded that the application of ludo game media has an effect on student learning outcomes in animalia material for class X IPA SMAN 8 Luwu Timur.